Penerapan Strategi Branding di Era Digital pada Vape Store Doyan Vape - Fajar Nur Romadhon; Sulartopo Sulartopo (Lembaga Pengembangan Kinerja Dosen, 2026)
The demand dynamics for electronic cigarettes or vapes in society show fluctuations influenced by various key factors, including government regulations, public health perceptions, lifestyle trends, and product innovations. With the limited availability of vape products in general retail stores, the establishment of vape stores has become a promising business prospect, driven by the shift in consumer preferences from tobacco cigarettes. This research aims to formulate effective branding strategies and promotional materials to address the image and marketing challenges faced by Doyan Vape, a vape store operating in Grobogan, Central Java. Since its establishment in 2020, Doyan Vape has faced difficulties, particularly due to a weak logo design that lacks a unique identity and includes elements already patented by another brand. Another issue is the minimal promotional activities that are engaging. The methodology focuses on brand identity development and communication media. The proposed solutions include redesigning the logo to meet strong branding criteria and creating supporting promotional media such as merchandise, as well as optimizing Instagram ads with more informative and transparent content to specifically reach the adult target audience. It is expected that the outcome of this branding strategy design will enhance the appeal and commercial value of Doyan Vape, ultimately having a positive impact on increasing sales volume and business development.